Strategi Meningkatkan Efektivitas Grebeg Suro sebagai Media Pewarisan Budaya Reog Ponorogo pada Generasi Muda - Yunita Ayu Fatmawati; Maria M Widiantari; Fikri Hasan (KOLONI, 2026)
Reog Ponorogo has been recognized as a UNESCO Intangible Cultural Heritage in Need of Urgent Safeguarding, emphasizing the critical need for structured transmission. The annual Grebeg Suro festival serves as a pivotal cultural communication channel to preserve this heritage among the younger generation. This study aims to analyze the current effectiveness of Grebeg Suro as a cultural transmission medium, identify its supporting and hindering factors, and formulate communication strategies to enhance engagement. Utilizing a descriptive qualitative approach, data were gathered through semi-structured in-depth interviews with eight informants: a cultural figure, an art teacher, a festival practitioner, and five representatives of the youth generation (ranging from passive viewers to active performers). Data analysis followed the interactive model of Miles and Huberman. The findings reveal a significant gap across communication dimensions: while cognitive and affective engagement remain remarkably high, active behavioral engagement remains limited, with many youths operating merely as passive spectators. Hindrances include excessive event durations that diverge from modern consumption patterns, administrative and budget blockages, and horizontal peer pressures labeling traditional arts as archaic. Conversely, strong institutional backing and the global prestige of UNESCO serve as vital facilitators. Grounded in Lasswell’s and Wilbur Schramm’s communication models, this study proposes an integrated strategy comprising digital co-creation, bidirectional social feedback loops, choreography adaptation, and structural youth-led committees to reduce the dissonance between presence and active participation.